ight to Education and Hospital Class: An Approach on the Institutional Guarantee of Pedagogical Practice Developed in Extracurricular Environments (Interdisciplinary Studies Journal, 2021)
We propose an approach and consequent expansion of discussions regarding hospital class as a system that guarantees the right to education for children and adolescents in situations of illness and hospitalization. Initially, it is important to highlight that the right to education is guaranteed by the 1988 Federal Constitution. Based on this supreme regulation—also utilizing the Child and Adolescent Statute of 1990—we aim to understand how the provided regulations are foundational to the activity and consolidation of hospital class as an important tool for enabling the educational access of children and adolescents who are temporarily excluded from regular (in-person) activities due to health issues. Although conducted in an extracurricular environment, the pedagogical actions developed in hospital class are based on formal education, meaning they must have systematization, an organized pedagogical framework, and, most importantly, be carried out under official responsibility. Thus, from a theoretical approach (bibliographic study), we examine the hospital class not only as part of a fundamental right for the targeted group but also as a definitive duty of the State—which characterizes education, beyond an institutionalized prerogative, as a system that is essential for the cognitive, intellectual, and social development of the citizen. Our interest lies primarily in observing the establishment of a structure that operates independently and is guided by principles of inclusion (humanization)—thus serving the purpose of maintaining social justice. Therefore, we can preliminarily conclude that the right to education guaranteed in the hospital class involves the dimension of ensuring dignity and subjectivity for the individual in the hospital environment (Ceccim, 1999). It is necessary, in final remarks (though not conclusive), to note that our study is based on the realization that this topic is still insufficiently explored in the knowledge areas with which it relates—Law, Education, and Psychology—and for this reason, we propose this theoretical effort.
Keywords: Hospital Class; Right to Education; Child and Adolescent; Humanization